Enderleina preclara Jewett, 1960 (Plecoptera, Perlidae), from the Venezuelan Guayana—A description of a putative female, nymph and egg - Derka, Tomáš; de Figueroa, J. Manuel Tierno; Čiampor, Fedor Jr. (Zootaxa, 2019)
The putative female, nymph and egg of Enderleina preclara are described from specimens collected in the Kukenán-tepui foothills and Acopán-tepui foothills and plateau of Venezuela. Morphological and molecular approaches were employed to characterize these stages. Diagnostic keys for males and females of the described Enderleina species are also presented. The nymph is also morphologically compared with those of other Enderleina species. Comments on the ecology of this species and erroneous information regarding the putative type locality of E. preclara are provided.